Simulation Models of Fuel Cell Systems - Md. Shah Majid, author 265987; Fakulti Kejuruteraan Elektrik 540663 (Johor Bahru, Johor : PENERBIT UTM PRESS, 2008)
The research activity aimed to analyse and model fuel cell systems for stationary applications. In particular, PEM and SOFC models have been developed and set up in the Matlab-Simulink© environment. In the paper, the steady state and dynamical operation of PEM and SOFC technologies have been analysed, and their main characteristics have been compared, e.g. the response to the air and hydrogen flow rate and pressure regulation.